2020
DOI: 10.1101/2020.08.06.234906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paranode stability requires UNC5B expression by oligodendrocytes

Abstract: Netrins are secreted proteins that direct cell migration and axon extension in the developing CNS and are essential for normal neural development. In the mature CNS, netrin-1 is expressed by neurons and oligodendrocytes and implicated in the stability of axo-oligodendroglial paranodal junctions. Here we report that the netrin receptor UNC5B is highly expressed by mature oligodendrocytes and enriched at paranodes. We demonstrate that paranodes become disorganized following conditional deletion of UNC5B in oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…Netrin-1 and its receptors are required for the maintenance of paranodal junctions in the mature CNS (Bull et al, 2014;de Faria et al, 2020;Jarjour et al, 2008). Here, we showed that focal netrin-1 signaling is sufficient to remodel the local distribution of myelin proteins PLP and CNP near the bead surface, and recruit paranodal proteins DCC (Bull et al, 2014;Jarjour et al, 2008), NF155 (Bhat et al, 2001;Boyle et al, 2001;Charles et al, 2002;Pillai et al, 2009;Sherman et al, 2005) and ZO-1 (Ogawa & Rasband, 2009;Poliak et al, 2002).…”
Section: Netrin-1-mediated Adhesion Directs Local Reorganization Ofmentioning
confidence: 84%
See 1 more Smart Citation
“…Netrin-1 and its receptors are required for the maintenance of paranodal junctions in the mature CNS (Bull et al, 2014;de Faria et al, 2020;Jarjour et al, 2008). Here, we showed that focal netrin-1 signaling is sufficient to remodel the local distribution of myelin proteins PLP and CNP near the bead surface, and recruit paranodal proteins DCC (Bull et al, 2014;Jarjour et al, 2008), NF155 (Bhat et al, 2001;Boyle et al, 2001;Charles et al, 2002;Pillai et al, 2009;Sherman et al, 2005) and ZO-1 (Ogawa & Rasband, 2009;Poliak et al, 2002).…”
Section: Netrin-1-mediated Adhesion Directs Local Reorganization Ofmentioning
confidence: 84%
“…Netrin-1 is expressed by myelinating oligodendrocytes and locally enriched at central nervous system (CNS) paranodes (Bull et al, 2014;Jarjour et al, 2008;Manitt et al, 2001;Manitt, Thompson, & Kennedy, 2004). Selective deletion of the netrin-1 receptors deleted in colorectal carcinoma (DCC) or UNCoordinated-5 homologue B from oligodendrocytes severely disrupts paranodal junctions (Bull et al, 2014;de Faria et al, 2020). Emerging evidence indicates that netrins influence the formation of epithelial cell-cell junctions (Beamish, Hinck, & Kennedy, 2018), and direct the local recruitment of synaptic proteins and formation of synaptic specializations in neurons (Colon-Ramos, Margeta, & Shen, 2007;Goldman et al, 2013;Lai Wing Sun, Correia, & Kennedy, 2011;Poon, Klassen, & Shen, 2008).…”
Section: Introductionmentioning
confidence: 99%